The mechanism of restructuring of surfactant monolayer on mica surface in aqueous solution: molecular dynamics simulation. Issue 5 (24th March 2018) - Sun, Jichao; Shi, Jing; Zhang, Peili; Yuan, Shiling
Abstract: Molecular dynamics simulation was employed to investigate the restructuring process of CTAB monolayer at mica/water interface. The reversing process of CTAB monolayer was exploited by diffusion of water molecules, reversing of CTAB molecules with time evolution and restructuring of the surfactant monolayer. The results showed that bromide ions around surfactant head groups diffused into bulk water readily due to the electrostatic repulsion caused by negatively charged mica surface. Meanwhile, because of the electrostatic attraction between water molecules and mica surface, part of water molecules can penetrate the surfactant monolayer to form water channel which bridges bulk water and mica surface. The monolayer structure was disturbed by diffusion of bromide ions and formation of water channel. Few of the head groups of surfactants tended to reverse and enter into aqueous solution. The number of reversed surfactant molecules increased with time evolution. The monolayer restructured into bilayer structure gradually. Finally, a cylindrical aggregate was obtained.